Can grants affect student performance? Evidence from five Italian universities. Issue 1 (2nd January 2021) - Graziosi, Grazia; Sneyers, Eline; Agasisti, Tommaso; De Witte, Kristof
ABSTRACT: This paper assesses the effect of need-based grants on the performance of university students in Italy. We performed a series of between-universities and within-universities propensity score matching analyses to evaluate the effect of grants on several student performance indicators, such as dropout rate, first year credits and efficiency of study. Our findings suggest that financial aid has a positive, substantial and statistically robust effect on university students' performance and on if and when they complete their undergraduate degree courses. The positive impact is heterogeneous across universities, while few differences were detected for subgroups of students. Reinforcing financial aid policies can simultaneously help disadvantaged students and improve overall academic performance in Italian universities.